The association between metal element levels and thyroid nodules in oilfield workers: a cross-sectional study - Wen, Xinyue; Deng, Feidan; Qiao, Lichun; Li, Miaoqian; Wang, Xining; Li, Hongqiu; He, Huifang; Xie, Yanjun; Li, Zhaoyang; Yang, Bowei; Han, Jing (Frontiers in Endocrinology, 2025)
BackgroundMetal elements affect the physiological processes of the thyroid gland and are associated with the formation of thyroid nodules (TNs). This study aimed to investigate the relationship between metal element levels and TNs in oilfield workers and to provide a preliminary scientific basis.MethodsThe study used a cross-sectional study to collect relevant data in 2022. Spearman’s rank correlation was used to analyze the correlation between multiple metal elements. The Logistic regression model and Weighted Quantile Sum (WQS) regression model were used to analyze the association between metal elements and the prevalence of TNs.ResultsA total of 517 oilfield workers were included in this study and the prevalence of TNs was 40.62%. Sex, age, and uric acid levels differed between the two groups (P < 0.05). The correlation analysis showed that most of the metals were correlated with each other to varying degrees. The WQS regression model showed that mixed exposure to seven metal elements was positively associated with the risk of developing TNs. In the total population and males, iron (Fe) and copper (Cu) levels were positively related to the risk of TNs prevalence (P < 0.05).ConclusionsTNs was found to be very prevalent among oilfield workers. Mixed exposure to metal elements may be associated with an elevated risk of TNs, with Fe and Cu emerging as potential contributors to this association.